2015
DOI: 10.1093/eurheartj/ehv292
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative defibrillation testing and clinical shock efficacy in patients with implantable cardioverter-defibrillators: the NORDIC ICD randomized clinical trial

Abstract: AimsThis trial was designed to test the hypothesis that shock efficacy during follow-up is not impaired in patients implanted without defibrillation (DF) testing during first implantable cardioverter-defibrillator (ICD) implantation.Methods and resultsBetween February 2011 and July 2013, 1077 patients were randomly assigned (1 : 1) to first time ICD implantation with (n = 540) or without (n = 537) DF testing. The intra-operative DF testing was standardized across all participating centres, and all ICD shocks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 27 publications
4
63
0
8
Order By: Relevance
“…However, EEG recovery occurs within less than 30 seconds, with a [216] 540 DT ICD shocks were programmed to 40 J in all patients. Primary endpoint: first shock efficacy for all true VT and fibrillation episodes during 22.8 months of follow-up.…”
Section: Dt-related Complicationsmentioning
confidence: 99%
“…However, EEG recovery occurs within less than 30 seconds, with a [216] 540 DT ICD shocks were programmed to 40 J in all patients. Primary endpoint: first shock efficacy for all true VT and fibrillation episodes during 22.8 months of follow-up.…”
Section: Dt-related Complicationsmentioning
confidence: 99%
“…39 Defibrillation efficacy was not different between both groups during followup. Similarly, in the SIMPLE trial of 2500 patients, routine defibrillation testing did not result in a reduction in arrhythmic deaths during a mean follow-up of 3.1 years.…”
Section: Implantable Cardioverter Defibrillator Therapy and Implant-bmentioning
confidence: 85%
“…The development for more advanced systems is ongoing, including dual- Implantable cardioverter defibrillator testing is no longer necessary during routine and uncomplicated ICD implantation: in the Nordic ICD Trial, 1077 patients were randomly assigned to first time ICD implantation with (n = 540) or without (n = 537) testing of defibrillation threshold. 39 Defibrillation efficacy was not different between both groups during followup. Similarly, in the SIMPLE trial of 2500 patients, routine defibrillation testing did not result in a reduction in arrhythmic deaths during a mean follow-up of 3.1 years.…”
Section: Leadless Pacemakersmentioning
confidence: 85%
“…10,12) The SIMPLE trial is a single blind, randomized, multicenter trial, evaluating the non-inferiority of non-testing versus testing using a composite outcome of arrhythmic death or failed appropriate shocks for ventricular arrhythmias. From its study, the authors concluded that routine DFT testing at the time of the ICD implantation is generally well tolerated but does not improve the shock efficacy or reduce the arrhythmic death.…”
Section: Discussionmentioning
confidence: 99%